Safety and efficacy of laparoscopic near‐total colectomy and ileo‐distal sigmoid anastomosis as a modification of total colectomy and ileorectal anastomosis for prophylactic surgery in patients with adenomatous polyposis syndromes: a comparative study. (28th January 2020) - Anele, C. C.; Nachiappan, S.; Sinha, A.; Cuthill, V.; Jenkins, J. T.; Clark, S. K.; Latchford, A.; Faiz, O. D.
Abstract: Aim: Colectomy in patients with adenomatous polyposis (AP) syndromes demands good oncological and surgical outcome. Total colectomy with ileorectal anastomosis (TC‐IRA) is one surgical option for these patients. Anastomotic leakage rates of 11% have been reported following TC‐IRA. Ileo‐distal sigmoid anastomosis (IDSA) is a recent modification of our practice. Our aim was to compare postoperative outcome in patients with AP following near‐total colectomy with IDSA (NT‐IDSA) and TC‐IRA at a single institution. Method: A prospectively maintained database was reviewed to identify patients with AP who underwent laparoscopic NT‐IDSA and TC‐IRA. Patient demographics, early morbidity and mortality and outcome of endoscopic surveillance were evaluated. Results: A total of 191 patients with AP underwent laparoscopic colectomy between 2006 and 2017, of whom 139 (72.8%) underwent TC‐IRA and 52 (27.2%) NT‐IDSA. The median age at surgery in the TC‐IRA and NT‐IDSA groups was 20 years (IQR 17–45) and 27 years (IQR 19–50), respectively. Grade II complications were comparable between the two groups. There were no anastomotic leakages in the NT‐IDSA group compared with 15 (10.8%) in the TC‐IRA group ( P = 0.0125) and no reoperation in the NT‐IDSA group compared with 17 (12.2%) in the TC‐IRA group ( P = 0.008). The frequency of polypectomies per flexible sigmoidoscopy was comparable between the two groups. Conclusion: This study demonstrates that laparoscopic NT‐IDSA for polyposis is associated with a significant improvement in anastomotic leakage rates and surgical outcome. It is too soon to tell whether NT‐IDSA alters the need for further intervention, either endoscopic polypectomy or further surgery.